Incidence of mortality due to malaria with typical and atypical presentation - Rathod, Shital N.; Chavan, Arvind; Sharma, Shilpa; Rathod, Tushar; Bavdhankar, Koustubh (International Journal of Advances in Medicine, 2018)
Background: Malaria, despite intensive efforts to control, remains a leading cause of morbidity and mortality in humans. India contributes to 61 per cent of malaria cases and 41 per cent of malaria deaths in SEAR countries. The objective of the present study was to find out an incidence of mortality due to malaria with typical and atypical presentation. Methods: The present was conducted over a period of three years. During the study period 630 patients with clinical suspicion of malaria were tested for malaria using peripheral smear, QBC and RDT. Results: The mortality rate in this study group 161 (25.55%) out of which maximum mortality observed in patients with falciparum malaria either singly or with mixed infestation. There is no significant correlation between the typical and atypical presentations in the different age groups with mortality. Conclusions: For timely diagnosis and treatment a high index of suspicion for the disease should be maintained by treating physicians, especially in endemic areas. They should be aware of the varied manifestations to minimize the mortality due to malaria.